(untitled) (Research, Society and Development, 2021)
Objective: To analyze reports of repeat violence in the state of Ceará. Methodology and Discussion: Descriptive, retrospective study with a quantitative approach. Data were collected from the DATASUS/SINAN database. Results: 6,942 cases of violence against women of childbearing age between 10 and 49 years were reported in the state of Ceará. Conclusion: The cycle of violence against women of childbearing age in Ceará continued even after notifications were registered.